Pengaruh Implementasi Rekam Medis Elektronik Dan Literasi Digital Petugas Terhadap Efisiensi Pelayanan Rawat Jalan - Diah Karlina (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Digital transformation of hospitals in Indonesia has accelerated following the Ministry of Health Regulation No. 24 of 2022 that mandates the adoption of Electronic Medical Records (EMR) in every healthcare facility. Nevertheless, the effectiveness of EMR in improving outpatient service efficiency remains inconsistent because it depends heavily on the digital literacy of health workers. This study aims to analyze the effect of EMR implementation and staff digital literacy on outpatient service efficiency at Mitra Sejati General Hospital. This research employed a quantitative analytical design with a cross-sectional approach. The population comprised 120 outpatient staff, and 92 respondents were selected through simple random sampling. Data were collected using a validated Likert-scale questionnaire (1–5) and analyzed through univariate, bivariate, and multiple linear regression tests supported by classical assumption testing. The results indicated that EMR implementation (β = 0.412; p = 0.000) and digital literacy (β = 0.368; p = 0.000) had a positive and significant effect on outpatient service efficiency, both partially and simultaneously (F = 58.734; p = 0.000), with an Adjusted R² of 0.559. The findings imply that strengthening EMR governance and continuous digital literacy training are strategic interventions for improving outpatient service efficiency in Indonesian hospitals.